Knowledge, knowledge mobilisation and the third sector. (7th July 2016) - Lang, Iain A; Hardwick, Rebecca
Abstract : This paper is about third sector organisations (TSOs) and how they use knowledge. Drawing from the emerging field of knowledge mobilisation, we argue that current policy and thinking about knowledge and TSOs too often employ a simplistic set of assumptions. We propose that there are many benefits to be had from taking an approach that acknowledges complexity and engages TSOs more deeply in knowledge production and use.